PENGARUH PAKAN PADAT GIZI TERHADAP TINGKAT DEHIDRASI TERNAK SAPI BALI SELAMA TRANSPORTASI DARI BULUKUMBA SULAWESI SELATAN KE BANJARMASIN KALIMANTAN SELATAN - Arga Arya Acmadi Awal; Khaerani Kiramang; Muhammad Nur Hidayat (State Islamic University (UIN) Alauddin, 2015)
ABSTRACT. This research aim to determine the influence of nutrient-dense diet on the leveof dehydration Bali`s cows cattle during transport from Bulukumba South Sulawesi ToBanjarmasin South Kalimantan. Type of research was experimental research done by habituation to the animal research is given for is days prior to transport. research site in Anrang Kab. Bulukumba South Sulawesi to Banjarmasin South Kalimantan for sample analysis was conducted In Laboratory Technology Livestock Products, HasanuddinUniversity of Nutritoinal Chemistry Laboratory of Animal Husbandry Faculty. Thesresult showed that distance and time of the research cows transportation from Anrang Kab. Bulukumba South Sulawesi to Banjarmasin South Kalimantan were respectively thetotal distance of 1350,83 km, while the total travel time was 2,5 hours and the result of thiresearch also showed that administration of Chromium Picolinat not show an influence onthe level of dehydration Bali `s cows throught the percentage of water content Bali cattle’feces on transport and the depreciation rate of Bali`s cows weight of the highest shown in cattle fed forage without UMMB was 7,47 %, while that given UMMB and UMMB whichwas around 3,58 % and 5,13 %.